2015
DOI: 10.1111/jnc.13105
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin1 modulates odorant‐evoked fear response via two serotonin receptor subtypes (5‐HT1A and 5‐HT2) in zebrafish

Abstract: Kiss1, a neuropeptide predominantly expressed in the habenula, modulates the serotonin (5-HT) system to decrease odorant cue [alarm substance (AS)]-evoked fear behaviour in the zebrafish. The purpose of this study was to assess the interaction of Kiss1 with the 5-HT system as well as to determine the involvement of the 5-HT receptor subtypes in AS-evoked fear. We utilized 0. 28 mg/kg WAY 100635 (WAY), a selective 5-HT 1A receptor antagonist, to observe the effects of Kiss1 administration on AS-evoked fear. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 51 publications
(124 reference statements)
3
59
0
Order By: Relevance
“…In zebrafish, AS-evoked fear stimuli significantly reduces Kiss1 and serotonin-related gene transcription (pet1 and slc6a4a), while intracranial kisspeptin administration suppresses AS-evoked fear responses (erratic movement and freezing) [36]. In subsequent studies, the authors observed that pharmacological blockade of serotonin receptors (5-HT 1A and 5-HT 2 ) removed this anxiolytic effect of kisspeptin [37] and that kisspeptin modulated the serotonergic system here primarily via glutamatergic neurotransmission [38]. Furthermore, selective inactivation of Kiss1 neurones (using kisspeptin conjugated to saporin) resulted in reduced Kiss1 immunoreactivity and Fos expression within the habenula and raphe (key structures in the fear response), which resulted in attenuated AS-evoked fear responses [36].…”
Section: Kisspeptin and Fearmentioning
confidence: 90%
See 2 more Smart Citations
“…In zebrafish, AS-evoked fear stimuli significantly reduces Kiss1 and serotonin-related gene transcription (pet1 and slc6a4a), while intracranial kisspeptin administration suppresses AS-evoked fear responses (erratic movement and freezing) [36]. In subsequent studies, the authors observed that pharmacological blockade of serotonin receptors (5-HT 1A and 5-HT 2 ) removed this anxiolytic effect of kisspeptin [37] and that kisspeptin modulated the serotonergic system here primarily via glutamatergic neurotransmission [38]. Furthermore, selective inactivation of Kiss1 neurones (using kisspeptin conjugated to saporin) resulted in reduced Kiss1 immunoreactivity and Fos expression within the habenula and raphe (key structures in the fear response), which resulted in attenuated AS-evoked fear responses [36].…”
Section: Kisspeptin and Fearmentioning
confidence: 90%
“…This included the anterior and posterior cingulate, amygdala, thalamus, and globus pallidus, which are all implicated in romantic, maternal, and unconditional love [53][54][55][56] and consistent with structures known to be involved in kisspeptin signalling in humans [19,20] and rodents [10,15,21,23,24]. Interestingly, kisspeptins enhanced activation of the amygdala in response to bonding images correlated with improved positive mood [40], a Sexual behaviours -Enhances limbic and paralimbic brain activity with correlations to reward, sexual aversion, and positive mood (H) [40] -Triggers erections (R) [51] Fear -Reduces fear responses (Z) [36][37][38]43] Social behaviours -MeA kisspeptin neurone apposition with dopaminergic and vasopressinergic neurones (R) [24] Audition -Male rodent ultrasonic vocalisations increase female ARC kisspeptin activity which correlates to the duration of female searching for male (R) [34] Mood -Antidepressant-like effects (R, H) [40,44] -Anxiolytic effects (R, Z) [31,36] -Anxiogenic effects (R) [42] Olfaction -Kisspeptin anatomical framework (R, H) [24] -Kiss1r and MeA Kiss1 roles in male olfactory partner preference (R) [30,31] -Opposite-sex urinary odours stimulate RP3V and limbic kisspeptin neurones and enhance LH surge (R) [32,33] Kisspeptin signalling potential mechanism that may contribute to the desire to bond with a partner.…”
Section: Kisspeptin and Sexual Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…alarm substance also increases plasma levels of norepinephrine, epinephrine, and glucose, effects which were blocked by fluoxetine (Maximino et al, 2014b). Both behavioural and autonomic effects, however, were not blocked by treatment with WAY 100,635 (Maximino et al, 2014b); interestingly, when animals are exposed to the alarm substance during the novel tank test, WAY 100,635 and methysergide (a 5-HT 2 receptor antagonist) potentiate the effect of alarm substance (Nathan et al, 2015).…”
Section: Monoaminergic Innervation In Teleostsmentioning
confidence: 97%
“…Alarm substance also increases plasma levels of norepinephrine, epinephrine, and glucose, effects which were blocked by fluoxetine (Maximino et al, 2014b). Both behavioural and autonomic effects, however, were not blocked by treatment with WAY 100,635 (Maximino et al, 2014b); interestingly, when animals are exposed to the alarm substance during the novel tank test, WAY 100,635 and methysergide (a 5-HT2 receptor antagonist) potentiate the effect of alarm substance (Nathan et al, 2015).…”
Section: Serotonin and The Aversive Behaviour Network Of Zebrafishmentioning
confidence: 97%